Class and conflict : revisiting Pranab Bardhan's political economy of India - Edited by Elizabeth Chatterjee; McCartney, Matthew, (ed.) (New Delhi Oxford University Press, 2020)
In 1984, Pranab Bardhan published his classic work The Political Economy of Development in India. It went on to become one of the most influential references on the political economy of development in the pre-reform period of independent India. Class and Conflict reflects on the enduring influence of Bardhans original publication in the context of post-liberalization developments in India. Drawing on their own world-leading research, the contributors to this volume engage with a wide range of issues, such as whether big business dominates India today, how subsidies retard economic growth, and how the middle classes are transforming politics.
Keywords: Politics and government; Economic development